Green lab concept: towards sustainable healthcare practices in Malaysia - Idris, Faridah; Samsudin, Intan Nureslyna (Universiti Putra Malaysia, 2024)
Clinical laboratories in the healthcare sector are notable contributors to CO₂ emissions due to high energy and resource demands. In Malaysia, where carbon emissions reached 298.53 million metric tonnes in 2022, adopting sustainable practices in clinical laboratories is increasingly critical. This paper explores the Green Lab Concept, which aims to reduce laboratories' environmental impact through energy efficiency, water conservation, waste management, and sustainable procurement. By aligning with Malaysia’s green technology policies, these practices have the potential to support national sustainability goals and global climate action targets. However, implementing green lab practices faces challenges, including financial constraints, resistance to change, and regulatory compliance requirements. Despite these obstacles, green lab initiatives could foster a culture of environmental responsibility and align laboratory practices with sustainable development goals. With focused stakeholder engagement and strategic implementation, Malaysia’s clinical laboratories may play a pioneering role in advancing sustainable healthcare practices.